2003
DOI: 10.1002/bip.10381
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform IR spectroscopic appraisal of radiation damage in Micrococcus luteus

Abstract: Fourier transform IR spectroscopy (FTIR) is used to analyze cells of Micrococcus luteus, the type species of the highly heterogeneous genus Micrococcus that belongs to the Micrococcaceae family. The cells of M. luteus, which is a Gram-positive and yellow-pigmented bacterium, are submitted to increasing doses of gamma radiation. Irradiation leads to the generation of reactive oxygen species that induce biochemical changes as shown in spectral profiles. Beyond a dose of 0.70 kGy, significant differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…None of the tools employed in this work has been able to discriminate between medical and environmental isolates within the NF group, although medical strains tended to cluster together in the FTIR dendrogram. This evidence confirms the high sensitivity of the metabolomic fingerprint in discriminating strains subject to different stressing conditions (Corte et al, 2012;Perromat et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…None of the tools employed in this work has been able to discriminate between medical and environmental isolates within the NF group, although medical strains tended to cluster together in the FTIR dendrogram. This evidence confirms the high sensitivity of the metabolomic fingerprint in discriminating strains subject to different stressing conditions (Corte et al, 2012;Perromat et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…The peak area ratio of bands at 1087 cm À1 and 1540 cm À1 (A 1087 /A 1540 ) is often used to illustrate the change of the DNA/ protein content of the cells. [36][37][38][39] A higher value of this ratio implies a higher DNA content. [36][37][38][39] The results shown in Table III suggest that the cellular DNA content was lower for thermophilic bacteria (0.30 6 0.10) compared to mesophilic bacteria (1.16 6 0.50) (p , 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…49,52,53 Our results confirmed these studies since we found a significant decrease in the frequency of the carbonyl group, indicating an increase in the number of hydrogen bonds. The lower DNA/ protein ratio might suggest that the cellular DNA content was lower for thermophilic bacteria [36][37][38][39] (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have since evolved to Raman spectroscopic studies of the effects of in-vitro proton irradiation of excised tissues [52], and radiotherapeutically irradiated (γ-radiation) tissue specimens [53][54][55]. Other studies with bacteria have investigated the effects of γ-radiation on Deinococcus radiodurans [56], Kocuria rosea [57]and Micrococcus luteus [58] with FTIR spectroscopy. Recently Gault et al have demonstrated the sensitivity of FTIR spectroscopy to apoptotic effects in γ-irradiated lymphocytes [59] and to molecular changes in HaCaT cells exposed to both γ-radiation and hydrogen peroxide [60], together with its sensitivity to biochemical alterations in HaCaT cells irradiated with α-particles delivered by micro-beams [61].…”
Section: Introductionmentioning
confidence: 99%